Motorcycle taxi transport service and accidents rate: a stochastic analysis in Popayan, Colombia (2021)
The objective of this document is to investigate the determinants of the number of accidents related to motorcycle taxation in the city of Popayán, Colombia. The lack of official information on this illegal economic activity led to an incidental sampling made up of 306 individuals, surveyed in the second half of 2019. Initially, a socioeconomic profile of the drivers is made and then a stochastic Poisson model inflated by zeros, due to the cover-up of the number of actual accidents by respondents. The profile of the motorcycle taxi driver in Popayán coincides with that of other Colombian cities, namely: he is a man of around 33 years old, head of the household, with low levels of education and with unstable previous or current jobs. It is concluded that the number of accidents decreases with age, the number of children or the level of education, while characteristics such as the type of motorcycle or health conditions increase them.